Cluster approach in the film industry - M. I. Kosinova; A. A. Gorshkova (Вестник университета)
The article consider the concepts of cluster and cultural cluster. The specifics of the cluster approach in film production are studied. The basic principles according to which film clusters exist are highlighted. The relationship between the state, companies that are directly involved in production, and companies that have direct and indirect influence at all stages of the creation of an audiovisual product. The work of regional film commissions, which are a guide between the state and film producers within the fixed territory, is considered. The models of regional cinema development in Russia are analysed. The analysis of the prerequisites for the creation of film clusters in the Russian regions is carried out. The key current problems in the regional cinema are identified. The main steps that regions need to take when developing a strategy for the comprehensive long-term development of regional film production are presented.